PEPETELA’S THE RETURN OF THE WATER SPIRIT AS A PARABLE OF THE POSTCOLONIAL CONDITION IN ANGOLA - Victor, Ogbeide O. (European Scientific Journal, ESJ, 2013)
Writing about a post-colonial society which has fallen in love with capitalist democracy in the face of a crumbling Russian empire, Pepetela argues in The Return of the Water Spirit that the common people who fought for independence have been marginalized in post-independence Angola as the ruling class, once socialist, now worship on the altar of greedy capitalism. This paper contends that in this novel, Pepetela asserts that good as the naked revolution is in confronting the selfish ruling elite, the mythic example of Kianda in reclaiming what rightly belongs to him points the way forward in the Angolan people’s quest for a genuine reclamation of their political voice. In the final analysis, this paper concludes, Angolan problems can only be truly solved by Angolan-bred ideas.